Giant Intracranial Aneurysm Presenting as Temporal Hemianopia: When the Eyes Reveal a Hidden Danger - Pertiwi, Annisa Nindiana; Nusanti, Syntia; Pintary, Marsha Rayfa; Dewiputri, Salmarezka; Ayuningtyas, Sita Paramita; Sidik, Muhammad (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2025)
Introduction: Giant intracranial aneurysms (GIA) are rare and deadly diseases due to the high risk of rupture. The purpose of this report is to describe a case of GIA presenting as temporal hemianopia. Case Report: A 52-year-old male presented with worsening blurry vision three weeks before admission. Visual acuity was light perception in the right eye and 6/18 in the left eye. Neuro-ophthalmic examination revealed a relative afferent pupillary defect in the right eye and bilateral optic atrophy. At the next visit, the visual acuity of the right eye recovered to 6/18. Visual field testing showed temporal hemianopia in the left eye and generalized depression in the right eye. Magnetic resonance imaging demonstrated a 0,4 cm x 2,5 cm x 1,9 cm saccular aneurysm, on the medial side of the left internal carotid artery (ICA). Discussion: A giant (diameter ≥2.5 cm) ICA aneurysm may compress the optic chiasm, leading to various stages of visual loss. Several factors are known to delicate balance between thrombogenesis and thrombolysis within the aneurysmal sac. Spontaneous intra-saccular thrombosis in an unruptured GIA may be induced by calcification within the atherosclerotic wall of the aneurysm and loss of elastic lamina. It is prone to occur in a narrow aneurysm neck (<0.4 cm). Thrombosis reduces the size of the aneurysm sac, in which the accumulated fluid is reabsorbed. This may explain the decompression effect on optic chiasm and spontaneous visual recovery. Conclusion: Intracranial aneurysms are a rare cause of optic chiasm compression but can still be considered in cases of temporal hemianopia.